Action irrationality, systemic practical irrationality, and the remedy in Kant - Merle, Jean-Christophe (Studia Kantiana, 2023)
In contrast to the well explored criteria of practical rationality in Kant’s philosophy, there is hardly any attempt to systematically examine the sources of practical irrationality in Kant. Yet, the development of the realm of reason among human beings depends on this core issue of his philosophy. Although Kant does not provide any comprehensive analysis of irrationality, one can distinguish three kinds of problems and sources of practical irrationality, related respectively to each of the three main dimensions of practical rationality: instrumental, practical (in a narrower sense), and systemic. Inquiring into these dimensions, this paper also explores the reasons why a lack of rationality remains even in individual actions out of duty, i.e. out of practical reason, and why only acting under an idea of systemic rationality makes possible the full achievement of rationality.